An investigation of knowledge management and intellectual capital on organizational performance in on-profit organizations: the context of Algerian waqf institutions - Abdelkader, Laallam (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2020)
The world is changing at a great pace and acceleration. This pace of acceleration has affected in turn the working environment of charitable institutions and organizations, especially the massive development witnessed in the fields of sciences and administration, as well as the development of the needs and expectations of society and beneficiaries. These changes have increased the need for institutional development and the adoption of appropriate leadership and management methods that enhance the ability to respond to the new requirements and to achieve a strong competitive position. Hence, the roles of science, knowledge and learning have emerged, in developing and adopting appropriate methods to manage and transfer knowledge and experience within an organization, and to make it available for everyone to share and exchange easily, through knowledge fountains and databases. This research aims to explore the impact of knowledge management (KM) and intellectual capital (IC) on the organizational performance (OP) of waqf institutions in Algeria. Another primary objective of this study is to shed light on the importance of KM and IC for the sustainability and efficiency of the waqf institutions. The study adopted the Intellectual Capital Theory (ICT) as an extension of Resource-based Theory (RBT) and Knowledge-based Theory (KBT), to explore the impact of factors affecting organizational performance (OP). This study has adopted a survey questionnaire to collect data from a total of 193 (out of 485 distributed questionnaires) Algerian waqf employees. The data was analysed using Statistical Package for Social Sciences (SPSS) for data screening purposes, and Partial Least Squares - Structural Equation Modeling (PLS-SEM) software for testing the path modelling and the relationship between the instruments. The finding of this study revealed that knowledge management enablers (KMEn) and knowledge management processes (KMPs) had no direct significant effect on OP, while IC had a positive and significant effect on OP. In addition, the findings revealed significant paths between KMEn and both KMPs and IC. It is also shown that IC perfectly mediates the relationship between both KMEn, KMPs and OP, providing a significant path which waqf institutions may consider for further development. Although KM practices and IC components are applied and present implicitly, or to varying degrees, in the waqf institutions in Algeria, still most do not consider them as a key source of competitiveness, survival and continuity. The findings of this study will provide insights for policy makers and waqf institutions, to consider investing in KM and IC in Algeria and other Muslim countries, with the hope of restoring the leading role of waqf in their societies.